Efeito de diferentes concentrações espermáticas sobre a fertilidade de éguas inseminadas com sêmen eqüino diluído, resfriado a 20°C e transportado - De Carvalho, Giovanni Ribeiro; Da Silva Filho, José Monteiro; Coelho Lima, Marcos Chalhoub; Oliveira, Henrique Nunes [UNESP]; Palhares, Maristela Silveira (My University, 1998)
One hundred and one estral cycles of 92 Mangalarga Marchador breed mares were analyzed to study the effect of different spermatic concentrations on different reproductive characteristics. The mares were inseminated with diluted equine semen, cooled at 20°C and transported: T1 - concentrations below 250×10 6 (177.58±41.74×10 6 viable spermatozoa per inseminate dose), T2 - concentrations between 250 and 350 10 6 sptz (315.51±20.78×106), and T3 - concentrations above 350×10 6 sptz (477.71±136.83×10 6). The conception rates in the first cycle were 43.75 (7/16), 57.89 (11/19) and 54.55% (18/33) for treatments 1, 2 and 3, respectively. After five cycles, the conception rates were 36.00 (9/25), 44.12 (15/34) and 54.76% (23/42) for treatments 1, 2 and 3, respectively. Concentrations of 177.58±41,74×10 6 viable spermatozoa per inseminate dose had moderate fertility index in a commercial program using cooled and transported semen.
Effect of different spermatic concentration on the fertility of inseminated mares with diluted equine semen, cooled at 20°C and transported
Keywords: Cooled semen; Equine; Spermatic concentration; Transported semen; Equidae